Retrieval practice as a way to enhance learning and transfer in a high school biology classroom - Ralph, Shannon M. (Kansas State University, 2020)
Educators often seek methodologies that enhance enduring knowledge for their students if their goal is to teach effectively. Students who strive to improve their own learning often use less effective study strategies as a way to improve long-term memory or content transfer. If the goal of education is to teach students how to retrieve information that they have learned in the past to solve a novel problem, then teachers and students could benefit from evidence as to which strategies support this process. The goal of this study was to investigate retrieval practice in the form of quizzing as a way to improve teaching and learning in a high school biology classroom. A pre-test was given to all of the student participants prior to instruction in the targeted unit. Two retrieval quizzes were administered to the treatment group while the control group was given a review sheet covering the same information over which to study. The instructor provided the same content and activities to all students throughout the three-week time frame in which the study took place. A post-test was given to all students at the conclusion of the learning unit, and the scores were used to determine the differences in the learning gains that occurred between the treatment and control groups. Statistical analysis revealed that there were no significant differences in the post-test scores between the two groups. The non-significant results could have been influenced by one or more of the limitations of the study such as the low number of participants, the short time frame of the study, or using a testing instrument without demonstrated reliability. It would be beneficial to conduct further studies in authentic classroom settings as a way to identify effective teaching and learning strategies.
Keywords: Retrieval practice; Testing effect; High school; Biology; Learning; Memory transfer